PENGELOLAAN SARANA DAN PRASARANA BERBASIS ADIWIYATA DALAM MENUMBUHKAN KARAKTER PEDULI LINGKUNGAN SISWA DI SMAN 1 DEWANTARA (PERSPEKTIF TEORI BEHAVIORISME) - Elvira; Sahdan (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This research aims to evaluate Adiwiyata-based facilities and infrastructure management at SMAN 1 Dewantara from a behaviorism theory perspective. Using a qualitative descriptive method, this study analyzes data obtained through interviews, observations, and documentation. The findings indicate that Adiwiyata-based facilities and infrastructure management at SMAN 1 Dewantara plays a significant role in fostering students' environmental care character through five integrated management aspects: planning, procurement, inventory, maintenance, and disposal. Participatory planning cultivates responsibility and ecological awareness, while student involvement in procurement strengthens a sense of ownership and creativity. Simple inventory processes encourage discipline and accountability, systematic maintenance trains students in discipline and cooperation, and the disposal of unusable facilities instills efficiency and accountability. From Skinner's behaviorism theory perspective, school facilities and activities act as stimuli that consistently trigger environmentally conscious behaviors, which are reinforced through positive reinforcement such as praise and tangible results. This approach forms sustainable habits and creates a school culture conducive to the effective development of student character.